Risk Factors of Physical Condition of House and Clean and Healthy Living Behavior (PHBS) to Tuberculosis in Kaluku Bodoa Health Center Area, Makassar City - Zaenab; Rafidah; , Haerani; Azizah, Nurfitriani (International Journal of Statistics in Medical Research, 2025)
Background: Tuberculosis remains the 10th leading cause of death globally, accounting for approximately 1.3 million fatalities. The physical conditions of a house, including ventilation, humidity, temperature, occupancy density, lighting, and Clean and Healthy Living Behavior (PHBS), are crucial factors that should be considered in relation to TB incidence. Objective: This study aims to analyze the relationship between house physical conditions and PHBS with the incidence of TB in the working area of the Kaluku Bodoa Public Health Center, Makassar City. Methods: This study employed an observational analytic design with a cross-sectional approach. The sample size for the study comprised 150 respondents. Data were processed using univariate analysis, presented in tables, and further analyzed descriptively and bivariately using the Chi-square test to determine the relationship between house physical conditions and CHLB with TB incidence in the working area of the Kaluku Bodoa Public Health Center, Makassar City. Results: There was a significant relationship between ventilation, lighting, occupancy density, and PHBS with TB incidence in the Kaluku Bodoa Public Health Center, Makassar City. At the same time, temperature and humidity were found to have an insignificant effect on TB incidence. Conclusion: The findings of this study can be used to guide government policies aimed at improving the quality of life for individuals with TB. Environmental health officers can implement intensive programs emphasizing the importance of handwashing, maintaining cleanliness, and ensuring proper ventilation to reduce the risk of TB transmission.